Silurian-Devonian Land-Sea Interaction within the San Rafael Block, Argentina: Provenance of the Río Seco de los Castaños Formation - Cingolani, Carlos Alberto (2017)
The Río Seco de los Castaños Formation (RSC) is one of the ‘pre-Carboniferous units’ outcropping within the San Rafael Block assigned to Upper Silurian–Lower Devonian age. We review the provenance data obtained by petrography and geochemical-isotope analyses as well as the U–Pb detrital zircon ages. Comparison with La Horqueta Formation is also discussed. The main components of this marine fine-grained siliciclastic platform are sandstones and mudstones. The conglomerates are restricted to channel fill deposits developed mainly at the Lomitas Negras location. A low anchizone for the RSC was indicated by illite crystallinity index. From the geochemical proxies described above (Manassero et al. in Devonian Change: Case studies in Palaeogeography and Palaeoecology. Geological Society, 2009) a provenance from an unrecycled crust with an average composition similar to depleted compared with average Upper Continental Crust is suggested. TDM ages are within the range of the Mesoproterozoic basement and Palaeozoic supracrustal rocks of the Precordillera-Cuyania terrane. εNd values of the RSC are similar to those from sedimentary rocks from the Lower Palaeozoic carbonate-siliciclastic platform of the San Rafael Block. These data suggest an Early Carboniferous (Mississipian) low-metamorphic (anchizone) event for the unit. It is correlated with the ‘Chanic’ tectonic phase that affected the Precordillera-Cuyania terrane and also linked to the collision of the Chilenia terrane in the western pre-Andean Gondwana margin. As final remarks we can comment that the studied RSC samples show dominant source derivation from Famatinian (Late Cambrian-Devonian) and Pampean-Brasiliano (Neoproterozoic-Early Cambrian) cycles. Detritus derived from the Mesoproterozoic basement are scarce. U–Pb data constrain the maximum sedimentation age of the RSC to the Silurian–Early Devonian.